2015
DOI: 10.1083/jcb.201504117
|View full text |Cite
|
Sign up to set email alerts
|

Prion-like domains in RNA binding proteins are essential for building subnuclear paraspeckles

Abstract: Paraspeckles are mammalian subnuclear bodies built on a long noncoding RNA and are enriched in RNA binding proteins with prion-like domains; two of these proteins, RBM14 and FUS, use these domains to hold paraspeckles together.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
314
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 301 publications
(337 citation statements)
references
References 43 publications
15
314
0
1
Order By: Relevance
“…Because RBM14 was purified from E. coli, it may lack posttranslational modifications necessary for interaction with EBER2 (Discussion). This notion is supported by the previous observation that phosphorylation of the C-terminal region of RBM14 is essential for protein-protein interactions (22).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Because RBM14 was purified from E. coli, it may lack posttranslational modifications necessary for interaction with EBER2 (Discussion). This notion is supported by the previous observation that phosphorylation of the C-terminal region of RBM14 is essential for protein-protein interactions (22).…”
Section: Resultssupporting
confidence: 77%
“…They are also essential for the formation of paraspeckles, which are subnuclear bodies consisting of more than 30 proteins that form on the long ncRNA nuclear paraspeckle assembly transcript 1 (NEAT1) (18)(19)(20). Interestingly, RRM proteins not only play roles in overlapping cellular processes, but can also act in concert with each other, as they exhibit physical interaction (21,22).Here, we isolated ribonucleoprotein (RNP) complexes containing both EBER2 and PAX5 with the goal of identifying the protein(s) that bridges their interaction. As in our EBER2 CHART experiments (3), we used an antisense oligonucleotide (ASO) complementary to one of the accessible sites in EBER2 for selection, followed by immunoprecipitation using anti-PAX5 antibodies; the selected RNP complexes were subsequently analyzed by mass spectrometry.…”
mentioning
confidence: 99%
“…Recently, low complexity domains in paraspeckle-localized proteins were implicated in the formation of this sub-nuclear body. 63 Although not yet demonstrated, it is likely that CB formation involves similar physical events. The process has been shown to be temperature-dependent, 64 for example, while p80-coilin, in common with other proteins shown to drive phase transitions, can self-associate, 25 binds RNA, 65,66 and contains a central low complexity region.…”
Section: Physical Properties Of Nucleoli and Cbsmentioning
confidence: 99%
“…Several groups have shown that multivalent proteins enriched with highly disordered domains are capable of forming liquid droplets in vitro that display many characteristic features of NBs, including fusion and fission events. 86,87,90,91,145 It has also been suggested that separation of nucleoli, paraspeckles 146 and Nuage bodies formed by DEAD-box helicase 4 (Ddx4) protein 86,147 is driven by these disordered domains-containing proteins. Coilin and its homologs are highly disordered but Arabidopsis thaliana-derived coilin is stabilized upon snRNA binding leading to multimerization in vitro, 114 which can be assumed to contribute to CB nucleation.…”
Section: Proteinmentioning
confidence: 99%